1996
DOI: 10.1002/art.1780390519
|View full text |Cite
|
Sign up to set email alerts
|

An epitope on Ki antigen recognized by autoantibodies from lupus patients shows homology with the sv40 large t antigen nuclear localization signal

Abstract: Objective. Epitopes on Ki antigen were analyzed using synthetic peptides, including KILT, a 16-mer peptide with an amino acid sequence homologous to the SV40 large T antigen nuclear localization signal (SV40 T NLS).Methods. In addition to KILT, 4 synthetic peptides, all potential epitopes on Ki antigen according to computer analysis, were prepared and tested for reactivity with 49 anti-Ki-positive lupus sera by enzymelinked immunosorbent assay.Results. Eighteen sera reacted with KILT, but not with other peptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The occurrence of anti-Ki antibodies in different clinical conditions could be tentatively explained by the reactivity of these antibodies with different epitopes of the same antigen as suggested by previous studies. 7,8 The main clinical features recorded in our study, independently from the clinical diagnoses, were skin involvement and sicca symptoms. Even if both sicca and Ro/SSA antibodies were frequently recorded in our cohort of patients, no specific association was observed between these clinical and laboratory features.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The occurrence of anti-Ki antibodies in different clinical conditions could be tentatively explained by the reactivity of these antibodies with different epitopes of the same antigen as suggested by previous studies. 7,8 The main clinical features recorded in our study, independently from the clinical diagnoses, were skin involvement and sicca symptoms. Even if both sicca and Ro/SSA antibodies were frequently recorded in our cohort of patients, no specific association was observed between these clinical and laboratory features.…”
Section: Discussionmentioning
confidence: 79%
“…5,6 Ki nuclear protein contains multiple epitopes recognized by different autoimmune sera 7 in particular, one epitope, mostly recognized by SLE sera, showed a sequence homologous to the SV40 large T antigen localization signal. 8 Different authors suggested a specific association with SLE, confirming a frequency of anti-Ki antibodies ranging from 6 to 20%, using double immunodiffusion (DID), counterimmunoelectrophoresis (CIE) or ELISA assays. 2,[9][10][11][12][13] However, anti-Ki were subsequently found in other autoimmune diseases such as systemic sclerosis, MCTD, vasculitides, 9,11 suggesting that this autoantibody should not be considered as a specific marker of lupus disease.…”
Section: Introductionmentioning
confidence: 95%
“…1,2,4,13,14 The incidence of anti-Ki antibodies in lupus sera was 6.7% by immunoprecipitation, 2 11.8% by DID, 1 18.9% by ELISA using recombinant Ki, 14 21.8% by ELISA using purified Ki, 4 and 16% by ELISA using KILT, 13 suggesting that the frequencies of anti-Ki antibodies depend on the immunoassay system. In our study, the immunoreactivity of anti-Ki sera (detected by DID) was tested by ELISA using KILT, purified Ki, or bNAX and by IB using purified Ki.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these results, 160 µg/ml KILT, 5 µg/ml bNAX, and 5 µg/ml purified Ki were the antigen concentrations and 1 : 1000 was the serum dilution. 13 For the ELISA, antigen diluted in 0.05 M carbonatebicarbonate buffer (pH 8.5) was added to the wells of an immunoplate II (Nunc, Roskilde, Denmark) and incubated overnight at 4°C. After the coating solution was removed, the plate was washed three times with PBS-Tween.…”
Section: Enzyme-linked Immunosorbent Assaymentioning
confidence: 99%
See 1 more Smart Citation